Determinants of Agri-Lending Among Financial Institutions in Kenya - Maloba, Michelle (Graduate School of Business (GSB), 2018)
This study seeks to examine the factors that influence Kenyan financial institutions’ lending behaviour towards the agricultural sector. Secondary panel data from 15 licensed financial institutions (commercial banks and deposit-taking microfinance institutions) for a period of 6 years (2011-2016) was used after which a panel multiple regression model was estimated using random-effects to examine the significant determinants of agri-lending by financial institutions. The study found that financial institution equity and risk on credit were negative and statistically significant in affecting the gross agricultural loans ratio while financial institution size, return on credit and financial institution liquidity were insignificant. As a result, the researcher recommends that financial institutions should devise better risk management strategies in order to reduce volume of non-performing loans in agriculture. Furthermore, the Kenyan Government should enforce the requirement that regulated financial institutions should hold a minimum of 10%-15% agricultural loans in their portfolios. This would steer larger banks to increase their investments in the agriculture given the economic benefits that the country would receive as a result.